2021
DOI: 10.21203/rs.3.rs-774800/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Electrolyte Concentrations and Blood Gas Values in Neonatal Calves With Diarrhea

Abstract: Portable blood analyzers, which recently have been introduced to veterinary medicine, can facilitate immediate identification of sick calves in livestock farms. However, no appropriate standard values exist for neonatal calves; therefore, reference values for adult cattle guide diagnosis and treatment of newborn calves. Our goal was to determine electrolyte, blood chemistry, and blood gas values from healthy calves and compare them to those for diarrheic calves, thus providing useful information for diagnosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…It was shown that in the case of dehydrated animals, that is, with a disturbed electrolyte balance, the heart rate increased and there were disturbances in the rhythm of this organ [ 86 ]. Such disturbances are often observed in calves with diarrhea [ 87 ]. Furthermore, there is an increase in the number of lymphocytes and eosinophilia, which may already indicate inflammation in the body [ 71 ].…”
Section: The Influence Of Electrolyte Disturbances On Animalsmentioning
confidence: 99%
“…It was shown that in the case of dehydrated animals, that is, with a disturbed electrolyte balance, the heart rate increased and there were disturbances in the rhythm of this organ [ 86 ]. Such disturbances are often observed in calves with diarrhea [ 87 ]. Furthermore, there is an increase in the number of lymphocytes and eosinophilia, which may already indicate inflammation in the body [ 71 ].…”
Section: The Influence Of Electrolyte Disturbances On Animalsmentioning
confidence: 99%